Peran Perempuan Terhadap UMKM Dalam Perspektif Hukum Ekonomi - Sri Widiarty, Wiwik (Universitas Ekasakti, 2024)
Abstract: Women play an important role in economic development, including in the Micro, Small and Medium Enterprises (MSME) sector. In Indonesia, women contribute significantly to MSMEs. However, women still face various obstacles in developing MSMEs. This research aims to analyze the role of women in MSMEs from an economic legal perspective. This study used qualitative research methods. The data collection technique in this research is literature study. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The research results show that women have an important role in MSMEs, both as business owners, workers and consumers. Women contribute to MSMEs in various aspects, such as production, innovation and networks. Economic law has an important role in supporting women's empowerment in the MSME sector. Economic law can provide legal protection for women in MSMEs, such as the right to access capital, the right to training and education, and the right to protection from discrimination.